Analisis Tingkat Akurasi Algoritma Novel Sebagai Metode Prediksi (Studi Kasus: Prediksi Harga Emas) - Riyadli, Hafiz; Arliyana, Arliyana (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2017)
Fuzzy method in the world of information and communication technology especially in the domain of intelligent systems, which one can be used to predictions/ forecasting. In this study the author will use the Novel Algorithm presented by Jasim, Salim and Ibraheem as a method to predictioning the Gold Price, the data source is retrieved from the http://www.kitco.com. Then the predictions result with Novel Algorithm will be comparing with fuzzy time series methods presented by Ruey Chyn Tsaur. Results of the predictions using Novel Algorithm, obtained a value of MAPE 0,0385(3,85%), while the Fuzzy Time Series Ruey Chyn Tsaur, obtained results of MAPE 0,0544(5,44%)